G376(P) Use of a paediatric e-mail account service in optimising community management and outpatient referrals. (24th May 2017) - Steele, L; Dhaliwal, J; Watson, M; Klaber, R; Coren, M
Abstract : Aims: Our paediatric e-mail service is managed by paediatric registrars and consultants to support community health regionally to better manage patients within the community. This has previously been shown to be effective in other specialties. We aimed to assess the utility of this service in helping to integrate primary and secondary care paediatric services. Methods: Retrospective review of 534 referrals to a general paediatric outpatient clinic (22/10/15–21/05/16) and 474 emails to the paediatric email account (01/01/15–09/09/15). Results: 10 of the 15 most common referrals to outpatients were also in the 15 most frequently asked email questions (Table 1). For email enquiries, general practioners (GPs) asked for advice on cause and/or investigations (31%), management (29%), whether referral was indicated (29%), interpretation of results (5%), whether a service was available (5%), and a second opinion (1%). Conclusion: The similarity of outpatient referrals and the paediatric email service suggests this service could be used more widely as an important component of models of integrated child health. Our experience over many years has shown that this works best in the context of other face-to-face working together including outreach clinics and MDTs.